Communication Research Methods in Postmodern Culture: A Revisionist Approach, 1st edition - Larry Z., Leslie (Routledge, 2020)
The second edition of Communication Research Methods in Postmodern Culture continues to explore research from a postmodern perspective. Typical qualitative and quantitative research methods are adjusted to fit the needs of contemporary culture. Each chapter is updated with new information and fresh examples. Included in the second edition is a new chapter on Internet and social media research.